KEMITRAAN PETANI TEBU RAKYAT MITRA KREDIT DENGAN PG. SEMBORO DI KABUPATEN JEMBER - Ami Retno Larasati; Triana Dewi Hapsari (University of Jember, 2020)
The partnership is an important solution in agriculture, especially in sugarcane commodities. The ideal partnership is profit and supports each other. But, the partnership process, in general, is inseparable from the existence of asymmetric information. Asymmetric information, also known as “information failure” occurs when one person has greater information than another in economic transactions. Asymmetric information can make low satisfaction with each other. The purpose of the research is to know-how about the satisfaction partnership that occurs between farmers and sugar factories. The last research problem is about the farmers' satisfaction index. It was analyzed by CSI and IPA. The farmer's satisfaction with credits KUR that analyzed by CSI showed 83,90%. It means that the result included in the excellent category. IPA analysis showed the attribute of disbursement of rendemen information and payment time of DO are the priority. CSI value of sugar cane farmers PKBL credit partners is 83.44%. This value is also in a very satisfying category. Based on the Importance and Performance Analysis (IPA) analysis, which includes attributing A (top priority), namely the attribute of credit fund disbursement, yield information and time of DO payment. Farmers' interest in these attributes is high but their implementation is still lacking. Keywords: Cane, Partnership Credit, Satisfaction Index, CSI, IPA.